ANALYSIS OF THE FAILURE OF NEW LEGISLATIVE CANDIDATES IN LEGISLATIVE ELECTION 2024 USING GROUNDED THEORY - Annisa Liestiani; Ayu Wulandari; Edoward N. Budiyanto; Jerry Heikal (PT. Media Akademik Publisher, 2024)
On 14 February 2024, Indonesia held the democracy party simultaneously in all regions, which included the general election for president, DPR RI, and DPRD for each regency or city. General elections are an important point in the democratic process where legislative candidates, both incumbent and new candidates, compete to get votes because the number of available legislative seats is limited compared to the legislative candidates who register. In fact, many new candidates fail to get the seats. Therefore, the purpose of this study is to pinpoint the predominant factors that contribute to the defeat of new candidates. This research uses a qualitative method with a grounded theory approach to understand phenomena through the process of data collection and analysis. Data analysis involved open coding, category development and themes emerging from the data. Through in-depth analysis, it was found that the coding scheme consisted of 39 codes that formed 8 categories and gave rise to 4 themes with a total frequency of 39. Based on the analysis, it can conclude that the pre-dominant factors that caused 5 (five) new legislative candidates to lose in the 2024 legislative election (although they have self-figure in society and expertise) were less effective in political campaign (22 of 39 codes or 56.4%) and lack of supporting systems (11 of 39 codes or 28.2%). While money politics and election system were not the main factors that caused the failure. The results of this study can be used as consideration for new legislative candidates in the future, who should plan their political campaigns and seek a lot of supporting systems to avoid defeat.